Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1038/ncomms6371
|View full text |Cite
|
Sign up to set email alerts
|

Orbital Asian summer monsoon dynamics revealed using an isotope-enabled global climate model

Abstract: The Asian summer monsoon dynamics at the orbital scale are a subject of considerable debate. The validity of Asian speleothem d 18 O records as a proxy for summer monsoon intensity is questioned together with the ultimate forcing and timing of the monsoon. Here, using the results of a 150,000-year transient simulation including water isotopes, we demonstrate that Asian speleothem d 18 O records are not a valid proxy for summer monsoon intensity only at the orbital timescale. Rather, our results show that these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
124
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(145 citation statements)
references
References 53 publications
(73 reference statements)
8
124
0
1
Order By: Relevance
“…The validity of speleothem oxygen isotope records as proxy for summer monsoon 609 intensity is still a matter of debate (Caley et al, 2014). Whereas Liu et al (2014) The SHL pollen-derived climate variables (this study) along with selected proxy records from 1210 the Western Pacific Ocean.…”
Section: Biomes Landscape Openness and Reconstructed Climate Variablmentioning
confidence: 99%
See 1 more Smart Citation
“…The validity of speleothem oxygen isotope records as proxy for summer monsoon 609 intensity is still a matter of debate (Caley et al, 2014). Whereas Liu et al (2014) The SHL pollen-derived climate variables (this study) along with selected proxy records from 1210 the Western Pacific Ocean.…”
Section: Biomes Landscape Openness and Reconstructed Climate Variablmentioning
confidence: 99%
“…He et al, 2004;Zhao et al, 2009a; Wang et al, 100 2010;Cai et al, 2010; Clemens et al, 2010; Zhang et al, 2011; Ran and 101 Feng, 2013; Li et al, 2014;Yang et al, 2014), and (iii) the role of other factors, including 102 ocean-atmosphere interactions, solar activity, and high-low-latitude interactions, on the 103 regional climate (e.g. Wang and Qian, 2009;Caley et al, 2014;Jin et al, 2014). 104…”
mentioning
confidence: 99%
“…Although a surface-cooling anomaly of the WNP is observed in spring (not shown in the figure) in our CAM/SOM simulation, the SST change is not significant in the eastern tropical Pacific. Internal oceanic feedback could significantly influence the monsoon response to precessional forcing (Caley et al 2014); this feedback is not accounted for in this study, and warrants further study.…”
Section: Concluding Remarks and Discussionmentioning
confidence: 99%
“…The datasets had to cover more than 400 years of the Holocene, between 10 000BP and present day, and had to have sufficient overlap with at least one other complementary record. Note that we did not consider individual speleothem δ 18 O time series for our analyses, as the attribution to precipitation or temperature may be ambiguous on long timescales [5]. Preliminary analyses indicated that individual cave speleothem time series correlated more strongly with the temperature reconstructions in the set of reconstructions, than with the rainfall reconstructions (not shown).…”
Section: Paleoclimate Datamentioning
confidence: 99%